CORRELATION BETWEEN STUDENTS’ CHARACTER AND ONLINE LEARNING ON MATHEMATICS LEARNING OUTCOMES OF STUDENTS AT SDN 5 PANJER, KEBUMEN DISTRICT, KEBUMEN REGENCY IN ACADEMIC YEAR OF 2020/2021. - Farikhah, Nur Alfi; Chamdani, Muhamad; Suryandari, Kartika Chrysti (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
AbstractDuring Covid-19 pandemic, the government had policy to do online learning as an alternative in learning process. It expected that online learning built students’ character. It predicted that students’ character and online learning contributed on students’ mathematics learning outcomes. The study aimed to examine positive correlation between students’ character and online learning on mathematics learning outcomes. The research was quantitative research with correlation method. The sampling technique was non probability sampling. The data analysis used SPSS version 25. The result showed that the correlation value between students' character and online learning on mathematics learning outcomes was 0.440. It concludes that there is correlation between students’ character and online learning on the mathematics learning outcomes of students at SDN 5 Panjer.Keywords: character, online learning, and mathematics